Political essay on the island of Cuba - Humboldt, Alexander von 1769-1859 (University of Chicago Press, 2011)
The research Alexander von Humboldt amassed during his five-year trek through the Americas in the early 19th century proved foundational to the fields of botany and geology. But his visit to Cuba during this time yielded observations that extended far beyond the natural world. This title presents a physical and cultural study of the island nation.